2013
DOI: 10.1159/000346236
|View full text |Cite
|
Sign up to set email alerts
|

NeuroAiD® (MLC601) and Amyloid Precursor Protein Processing

Abstract: Background: Amyloid precursor protein (APP) undergoes cleavage under physiological conditions, predominantly by α- and γ-secretases, to form the nonpathogenic sAPPα and p3 fragments. By contrast, amyloid-beta (Aβ) is produced via proteolytic cleavage by β- and γ-secretases. In Alzheimer's disease (AD), APP is preferentially processed via the amyloidogenic pathway, producing large amounts of Aβ that form the major constituent of senile plaques and tau-containing neurofibrillary tangles. Similarly, stroke patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 98 publications
1
15
0
Order By: Relevance
“…Similar with our result of icariin, cerebrolysin treatment significantly reduced the levels of Full-length APP in APP Tg mice 27. NeuroAiD®, also known as MLC601, obviously decreased full-length APP levels in APP transfected SH-SY5Y cells 28. In these reports, the authors did not explain the underlying mechanism of altered APP levels.…”
Section: Discussionsupporting
confidence: 77%
“…Similar with our result of icariin, cerebrolysin treatment significantly reduced the levels of Full-length APP in APP Tg mice 27. NeuroAiD®, also known as MLC601, obviously decreased full-length APP levels in APP transfected SH-SY5Y cells 28. In these reports, the authors did not explain the underlying mechanism of altered APP levels.…”
Section: Discussionsupporting
confidence: 77%
“…MLC601 has shown both neuroprotective and neuroregenerative properties in several controlled studies of ischemic injury to the brain [15, 16, 17]. It has been shown that MLC601 is a possible modulator of amyloid precursor protein processing and has implications as a putative therapeutic strategy for the treatment of post-stroke dementia and Alzheimer disease [18]. In our recent study [7], we compared the efficacy and safety of MLC601 with cholinesterase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…There is convergent evidence that overproduction, aberrant aggregation, and decreased elimination of different forms of amyloid beta protein are critical events in the pathogenesis of AD and, therefore, treatment development has focused on these processes [ 12 ]. In AD, APP is preferentially processed via the amyloidogenic pathway, producing large amounts of amyloid beta protein that forms the major constituent of senile plaques and tau-containing neurofibrillary tangles [ 22 ]. Since MLC601 has some neuroprotective effects, it is possible that it may exert its neuroprotective effects via the regulation of APP processing.…”
Section: Discussionmentioning
confidence: 99%
“…MLC601 is a possible modulator of APP processing. Lim et al [ 22 ] found that MLC601 induced a decrease in APP and enhanced the secreted forms of APPα release, suggesting that MLC601 may act by promoting the processing of APP via the nonamyloidogenic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation